An Analysis of Occupational Licensing Policies in Texas - Quarles, Judd H. (My University, 2016)
As the regulatory efforts of government continue to increase at all levels, more attention is being given to the public policy topic of occupational licensing. Decisions on whether or not to require occupational licensing should be made on a case-by-case basis, after considering the health and safety risks presented to the public, as well as the costs and benefits of such policies. This dissertation examined occupational licensing policies in Texas by using three methods: case studies of six occupational licensing proposals offered in recent sessions of the Texas legislature, an empirical study of occupational licensing in Texas, and an empirical study comparing occupational licensing policies for behavior analysts across the 50 states. The findings of the case studies revealed that legislators in Texas often make decisions on whether or not licensing should be required in an occupation with very little information about the health and safety risks to the public, instances of harm that have actually taken place, or the costs and benefits found where licensing is already required. In the empirical studies, it was found that the best predictor of whether or not licensing would be required for an occupation in Texas was the amount of other states requiring licensing for the same occupation. Despite the fact that health and safety concerns are one of the most commonly stated reasons for individuals and groups to support occupational licensing requirements, occupations with higher accident rates were not found to be a significant factor in whether or not an occupation is licensed in Texas. When comparing Texas to other states, the most significant variable in determining which of the 50 states will require occupational licensing for behavior analysts is the per capita membership numbers in groups who oppose occupational licensing requirements for behavior analysts.
Chapter I: INTRODUCTION 1 Chapter II: LITERATURE REVIEW 8 Public Interest Justifications for Occupational Licensing 8 Lack of Information 8 Externalities 11 States Acting to Protect Individuals 11 Economic Costs of Occupational Licensing 12 Reciprocity and Labor Force Mobility 12 Economic Costs of Training 15 Not Only Incompetent Practitioners are Screened Out 17 High Quality Services versus Cutting Out Some Services Completely 21 Effects on Individuals with Criminal Records 23 Rent Seeking by Groups Wishing to Be Licensed 23 Political Economy of Occupational Licensing 24 Existing Empirical Studies 28 Chapter III: METHODOLOGY 39 Part 1: Case Studies on Occupational Licensing in Texas: Anesthesiology Assistants, Associate Auctioneers, Forensic Analysts, Foundation Repair Contractors, Roofing Contractors, and Veterinary Technicians 39 Part 2: Empirical Study of Occupational Licensing in Texas 40 Dependent Variable: Licensing Requirement 43 Risk to the Public Posed by the Occupation 45 Political Influence 45 Number of Other States Requiring Licensing in the Occupation 47 Organizational Structure of Occupations 48 Part Three: Empirical Analysis of Occupational Licensing Across the United States 50 Licensing Requirements 54 Risk Posed to the Public by the Occupation 54 Political Influence and Organization 54 Political Opposition to Occupational Licensing 55 State-Specific Characteristics 56 Chapter IV: FINDINGS 65 Part One: Results of Case Studies 65 Anesthesiology Assistants 68 Associate Auctioneers 74 Forensic Analysts 77 Foundation Repair Contactors 81 Roofing Contractors 90 Veterinary Technicians 101 Chapter V: DISCUSSION 109 Part One: Conclusions-Case Studies 109 Part Two: Conclusions on Empirical Study of Texas Occupations 114 Part Three: Conclusions on Empirical Study of Occupational Licensing Across the United States 116 Part Four: Policy Recommendations 117 Part Five: Putting Together Findings 132 REFERENCES 137 APPENDIX A: Institutional Review Board (IRB) Protocol Exemption Report………145
Keywords: Political Science; Public Administration; Occupational licensing; Occupational regulation; Texas Legislature; Regulatory policy; Case study